2015
DOI: 10.1037/prj0000120
|View full text |Cite|
|
Sign up to set email alerts
|

The role of different stigma perceptions in treatment seeking and dropout among active duty military personnel.

Abstract: Different stigma perceptions were associated with treatment seeking and dropout. Further longitudinal research is needed to examine how stigma perceptions influence these important outcomes. Practitioners need to be aware of how different stigma perceptions can influence treatment seeking and potentially target stigma perceptions during treatment to prevent dropout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 31 publications
3
48
1
Order By: Relevance
“…Depressiveness was the strongest predictor of apply and harm, consistent with the finding of a previous research in individuals with SUD or PTSD (e.g., [16,24,57]). Core features of depression are low self-esteem and diminished hope [58]; thus, as described by Corrigan et al [6], "one of the difficulties (…) is sorting out the effects of self-stigma from those of depression because symptoms of depression fundamentally lead to diminished self-esteem".…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Depressiveness was the strongest predictor of apply and harm, consistent with the finding of a previous research in individuals with SUD or PTSD (e.g., [16,24,57]). Core features of depression are low self-esteem and diminished hope [58]; thus, as described by Corrigan et al [6], "one of the difficulties (…) is sorting out the effects of self-stigma from those of depression because symptoms of depression fundamentally lead to diminished self-esteem".…”
Section: Discussionsupporting
confidence: 79%
“…Patients with PTSD showed significantly higher internalized stigma scores than those without PTSD [33]. Self-stigma related to seeking treatment and the perception of being stigmatized by others correlated positively with depression, PTSD and functional impairment, while the latter was also positively correlated with alcohol problems [16]. These results show the potential impact of PTSD on self-stigma, although such effects were not observed in our study after controlling for depressive symptoms.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These perceptions continue, despite policies designed to encourage MSMs to seek treatment and data showing that military leaders generally support their subordinates accessing MHS (Gibbs et al., ; Westphal, ). Perceptions of stigma are likely to increase when an MSM experiences a mental health disorder (Britt, Jennings, Cheung, Pury, & Zinzow, ; Hoge et al., ; Kim et al., 2010, ). Hoge et al.…”
Section: Background and Significancementioning
confidence: 99%
“…Of a sample population of National Guard and Reserve service members reporting psychological problems, Britt et al (2011) found that only 42% had sought treatment. Most recently, Britt, Jennings, Cheung, Pury, and Zinzow (2015) found that only 40% of soldiers who acknowledged having a mental health issue sought treatment in the last year. Although the percentages of soldiers seeking treatment seem to be improving, the current literature continues to show less than half of those in need seek even a first visit with a mental health care provider.…”
mentioning
confidence: 99%